Vocational guidance – GPS for management of human resource development: does it work in Lithuania - Andriušaitienė, Daiva (Business, Management and Economics Engineering, 2020)
The purpose – of this article is to assess the vocational guidance situation and development opportunities in Lithuania. Research methodology – Systematic analysis of the peculiarities of vocational guidance; identification of the main problems and possibilities for vocational guidance through the development of a qualifications system based on the results of statistical analysis, expert assessment, data grouping and interpretation. Findings – Vocational guidance as an important subsystem of the educational system is being underemphasised and underfinanced, career counselling is pursued in a fragmentary manner, mainly through project-based initiatives which are not be based on systematic information. A way to improve vocational guidance is to organise it as an integrated information platform linked to the qualifications system. Research limitations – The main limitation is the lack of official statistics in vocational guidance. The systematic collection and publication of statistics would make it possible to quantify and analyse the factors of the current vocational guidance situation and their impact on the development of human resources. Practical implications – The obtained results are useful for social and economic and educational policy-making. Originality/Value – The article contributes to the scientific literature by presenting a model of vocational guidance development related to the development of the qualifications system, which would allow providing the necessary access to information.